Regulatory Challenges in International Aviation: Indonesia and Russia Compared - Gevan Naufal Wala; Lazarev Viktor Antonovich (PATTIMURA Legal Journal, 2025)
Introduction: The global aviation industry operates within a complex web of international regulatory frameworks that vary significantly from one country to another. This study focuses on the interplay between these frameworks, particularly examining the legal perspectives of Indonesia and the operational experiences of Russian pilots. Understanding these dynamics is crucial for identifying regulatory challenges that affect cross-border aviation operations. Purposes of the Research: The primary purpose of this research is to analyze the differences in aviation regulatory frameworks between Indonesia and Russia, with a focus on documentation requirements, certification recognition, and environmental regulations. By bridging theoretical legal examination with practical insights from aviation practitioners. Methods of the Research: This study employs a comparative legal analysis methodology, integrating theoretical frameworks with empirical data gathered from interviews and surveys of aviation professionals, including pilots and regulatory officials. The research examines documentation processes, certification practices, and environmental regulations in both jurisdictions, highlighting the operational implications for pilots navigating these regulatory landscapes. Results Main Findings of the Research: The findings reveal significant divergences in documentation requirements, with Indonesian authorities placing a strong emphasis on procedural compliance, while Russian frameworks prioritize technical standards. Certification recognition issues were found to increase operational costs by 4-7%, leading pilots to develop unofficial workarounds to address contradictory requirements. Additionally, environmental regulations exhibited stark differences; Indonesia's focus on noise abatement in densely populated areas contrasts sharply with Russia's emissions-oriented approach for Arctic operations. The research culminates in practical recommendations for regulatory harmonization that aim to reduce compliance burdens while maintaining safety standards across both jurisdictions.